Warung UMKM : Sarana Mengembangakan Jiwa Enterpreneur di Kalangan Remaja di Desa Sanrobone, Takalar - Herman Sjahruddin; Muh. Irfai Sohilaw; Hardiani Hardiani; Zulkarnain Basir; Andi Sulfati; Khaeril Khaeril; Elyas Albar; Heslina Heslina (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to foster and develop an entrepreneurial spirit among teenagers in Sanrobone Village, Takalar, through the optimization of Micro, Small, and Medium Enterprises (MSMEs) based on local potential. Teenagers are identified as strategic assets that need to be empowered for economic independence and job creation. The method of implementing this activity adopts a participatory and educational-practical approach, including the preparation stage, implementation of training and mentoring, and monitoring and evaluation. A total of 35 teenagers from Sanrobone Village were actively involved in a series of basic entrepreneurship training, identification of local business opportunities, technical production skills workshops, and simple digital marketing. The results of the activity showed a significant increase in teenagers' understanding of the concept of entrepreneurship from just selling to creating value. They succeeded in identifying 15 potential business ideas from local resources and 20 teenagers were able to produce product prototypes from these ideas. In addition, the initiative to form five micro-business groups initiated by teenagers is clear evidence of the growth of motivation and collaboration. In conclusion, this program is effective in laying a strong foundation for the development of a youth entrepreneurship ecosystem in Sanrobone Village, which is supported by the potential of natural resources and the enthusiasm of the participants. It is recommended that there be ongoing mentoring, facilitation of access to micro-capital, strengthening of networks, and integration of entrepreneurship curriculum in schools to ensure the sustainability and long-term impact of the program.